155k views
3 votes
4/3 (2x/3 + 1/2) = x/6 - 5/3

User Artholl
by
4.4k points

1 Answer

6 votes

The value of x is
-(42)/(13)

Explanation:

The expression is
(4)/(3) ((2x)/(3) +(1)/(2) )=(x)/(6) -(5)/(3)

To find the value of x, we need to simplify the equation,

Multiply the term
((2x)/(3) +(1)/(2) ) by
(4)/(3),


(8x)/(9) +(4)/(6) =(x)/(6)-(5)/(3)

Subtracting by
(x)/(6) and
(4)/(6) on both sides of the equation, we get,


(8x)/(9) -(x)/(6) =-(5)/(3)-(4)/(6)

Taking LCM on both sides,


(48x-9x)/(54) =(-10-4)/(6)

Simplifying, we get,


(39x)/(54) =-(14)/(6)

Multiplying both sides by 54,


39x=(-14(54))/(6) \\39x=-14(9)\\39x=-126

Dividing both sides by 39, we get,


x=-(42)/(13)

Thus, the value of x is
-(42)/(13)

User Mario Hendricks
by
5.0k points